ANALISIS KELAYAKAN USAHA PEMBIBITAN LAI (Durio Kutejensis) DI DESA BATUAH KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - Arista Damayanti; Ovigeria Subroto Sinaga (Jurnal Magrobis, 2013)
Arista Damayanti,Ovigeria S. Sinaga. Feasibility Analysis Of Lai Seedling(Durio kutejensis) in Batuah Village at Loa Janan District Kutai KartanegaraRegency.This research implementation in November until December 2012. Therespondent was Gapoktan Borneo Hijau in Batuah Village at Loa Janan District KutaiKartanegara Regency. The purpose of this study was to determine feasibility of Laiseedling in gapoktan Borneo Hijau was feasible or not.The result of the study NPV was Rp 282,996.33 > 0 this meaning that theeffort was feasible. Net B/C was 2,7 >1 this meaning that the effort was feasible. IRRwas 44,9 bigger than the value of interest 16%, this meaning that the effort wasfeasible.The value of Payback periode is 5,5 years its means the value less than timeproject, this meaning that the effort was feasible.Keyword : Seedling, Feasibility Analysis, Lai